SMART CITY POLICIES IN REGIONAL PUBLIC SERVICES IN INDONESIA: A SYSTEMATIC LITERATURE REVIEW - Siti Nurhidayah; Sandy Kurniawan (Journal of Contemporary Public Administration, 2026)
Smart City implementation in Indonesia serves as a strategic response to complex urban challenges, yet current execution remains fragmented, sectoral, and hindered by a significant digital divide. This study aims to conduct a comprehensive mapping of Smart City policy dynamics and their contribution to regional public service quality by identifying core research themes, evaluating impacts on efficiency, and uncovering neglected research gaps. The methodology follows a Systematic Literature Review (SLR) approach guided strictly by the PRISMA 2020 protocol, analyzing academic literature published between 2019 and 2025 across international and national databases, including Scopus, ScienceDirect, and Google Scholar. The selection process utilized rigorous inclusion and exclusion criteria, integrating bibliometric analysis via VOSviewer with qualitative thematic synthesis to ensure transparency and reproducibility. Findings reveal a fundamental paradigm shift from technocentric, infrastructure-heavy models to humanistic agile governance frameworks that prioritize public value and ecological sustainability through Green Smart City concepts. However, the study highlights critical structural constraints, including a persistent Java-centric geographical imbalance, internal bureaucratic silos, and a lack of system interoperability, which have led to a proliferation of redundant digital applications. Results indicate that while 70% of reviewed articles report improved service transparency, the long-term sustainability of these initiatives depends heavily on institutional capacity and digital leadership. This research concludes that synchronizing regional strategies with the National SPBE Architecture, as mandated by Presidential Regulation No. 132 of 2022, and adopting inclusive models such as Smart Villages and citizen-centric Co-creation are essential to mitigate regional service disparities and ensure digital transformation creates genuine public value for all citizens.